Muscle Synergies in Patients With Multiple Sclerosis Reveal Demand-Specific Alterations in the Modular Organization of Locomotion - Janshen, Lars (Front Hum Neurosci, 2021)
For patients with multiple sclerosis (MS), deficits in gait significantly reduce the quality of life. Using the concept of muscle synergies, this study investigated the modular organization of motor control during level and inclined walking in MS patients (MSP) compared with healthy participants (HP) to identify the potential demand-specific adjustments in motor control in MSP. We hypothesized a widening of the time-dependent activation patterns (motor primitives) in MSP to increase the overlap of temporally-adjacent muscle synergies, especially during inclined walking, as a strategy to increase the robustness of motor control, thus compensating pathology-related deficits. We analyzed temporal gait parameters and muscle synergies from myoelectric signals of 13 ipsilateral leg muscles using non-negative matrix factorization. Compared with HP, MSP demonstrated a widening in the time-dependent coefficients (motor primitives), as well as altered relative muscle contribution (motor modules), in certain synergies during level and inclined walking. Moreover, inclined walking revealed a demand-specific adjustment in the modular organization in MSP, resulting in an extra synergy compared with HP. This further increased the overlap of temporally-adjacent muscle synergies to provide sufficient robustness in motor control to accomplish the more demanding motor task while coping with pathology-related motor deficits during walking.